Pengembangan Sistem Informasi Persediaan Barang Berbasis Web di CV Kunikita - Anaziah, Suni; S Pasaribu, Johni (Jurnal ICT : Information Communication & Technology, 2021)
CV. Kunikita is a distributor in Garut city which is engaged in online sales for various product categories, namely food, fashion and skincare. As a distributor in the field of online sales, the management of storage of goods in the warehouse of CV. Kunikita is still by hand, that is, it is written in a ledger so that inventory information is not accurate. For this reason, it is necessary to use communication information technology in warehouse inventory management, no longer written in a ledger where this will result in data mismatches. The data collection method in this study is a qualitative descriptive method, and the methodology for developing this application is the waterfall SDLC method with black box testing and white box testing. Web-based information system application at CV. Kunikita with a database as a data storage facility that makes data processing and storage more efficient and useful for reporting data on warehouse inventory so that it can quickly take action to fill the warehouse inventory.